Impact of thermal processing on phytochemical profile and cardiovascular protection of Beta vulgaris L. in hyperlipidemic rats - Engy Mohsen; Marwa I. Ezzat; Ibrahim E. Sallam; Dalia Zaafar; Aya Y. Gawish; Yasmine H. Ahmed; Ahmed H. Elghandour; Marwa Y. Issa (Scientific Reports)
Abstract Beetroot (Beta vulgaris L.) is globally recognized for its outstanding color and flavor. It has been acknowledged for its therapeutic value since the ancient Romans. It is used to treat cardiovascular disorders. The therapeutic benefits of red beetroot are due to the substantial amounts of various bioactive metabolites, such as ascorbic acid, carotenoids, nitrates, phenolics, and betalains. However, the bioavailability and shelf life of these substances are significantly affected by the considerable variations in their processing methods among different countries. The longevity of the extracts is prolonged by employing well-established preservation techniques, such as boiling and steaming, which involve the application of heat. Our study aimed to analyze and compare the phytochemical composition of raw and heat processed beetroot using UPLC-QTOF-MS/MS. In addition, the study aimed to assess the effectiveness of processed beetroot in protecting against cardiovascular complications in a rat model of obesity induced by high-fat diet (HFD). UPLC-QTOF-MS/MS phytochemical profiling revealed the presence of 51 compounds, including organic acids, flavonoids, phenolics, betanins, and saponins. All the extracts demonstrated a significant decline in MDA, TNF- α, and IL-6 levels, suppressed the TGF-β expression, and restored the serum catalase level to normal. Among all the tested extracts, the steamed extract exhibited the slightest percentage change in body weight (10.2 ± 6.4) and effectively lowered the TNF-α level to normal levels. In contrast, the normal histological structure of heart muscle fibers was notably preserved in the cardiac sections of rats pretreated with steamed and boiled beetroot extracts. Additionally, mild caspase-3 immunoreactivity was observed in the cardiac muscles. The current study demonstrated that the steamed beetroot extract showed improved cardioprotective properties compared to the fresh and boiled extracts.